Evaluating polymer-supported isothiourea catalysis in industrially-preferable solvents for the acylative kinetic resolution of secondary and tertiary heterocyclic alcohols in batch and flow. Issue 19 (13th September 2018) - Guha, Nitul Ranjan; Neyyappadath, Rifahath M.; Greenhalgh, Mark D.; Chisholm, Ross; Smith, Samuel M.; McEvoy, Megan L.; Young, Claire M.; Rodríguez-Escrich, Carles; Pericàs, Miquel A.; Hähner, Georg; Smith, Andrew D.
Abstract : Highly recyclable isothiourea catalysts on various polymer supports are reported for the kinetic resolution of alcohols. Abstract : Polymer-supported Lewis base catalysts, based on the homogeneous isothioureas HyperBTM and BTM, have been synthesised and applied for the acylative kinetic resolution of secondary and tertiary heterocyclic alcohols. In batch, the use of industrially-preferable solvents was investigated, with dimethyl carbonate proving to be most generally-applicable. Significantly, the HyperBTM-derived immobilised catalysts were readily recycled, with no loss in either activity or selectivity. In addition to the kinetic resolution of secondary benzylic, propargylic, allylic and cycloalkanol derivatives, a range of 22 tertiary heterocyclic alcohols, based on privileged 3-hydroxyoxindole and 3-hydroxypyrrolidinone substructures, were resolved with up to excellent selectivity ( s = 7–190). Finally, the immobilised isothiourea catalysts were applied in a packed bed reactor to demonstrate the first example of the kinetic resolution of tertiary heterocyclic alcohols in a continuous flow process. High selectivities were obtained for the resolution of 3-hydroxyoxindole derivatives in ethyl acetate ( s up to 70); and for 3-hydroxypyrrolidinones derivatives in toluene ( s up to 42).